Results of Onlay Preputial Flap Urethroplasty for the Single-Stage Repair of Mid- and Proximal Hypospadias - González, Ricardo; Lingnau, Anja; Ludwikowski, Barbara Magda (Frontiers in Pediatrics, 2018)
Aims: To report current results of preputial flap onlay urethroplasty using the principle of the total preputial flap (TPF) for the one stage repair of mid- and proximal hypospadias. Methods: Retrospective chart review of patients in a prospectively kept data base of all hypospadias operations performed at 2 institutions from January 1st 2011 to August 2017 2016. Inclusion criteria: all patients who underwent hypospadias repair using a preputial only flap urethroplasty based on the principle of the total preputial flap. Demographic data, duration of follow-up, complications and reoperations were recorded. A successful result was considered to be a straight penis, a glanular meatus, absence of voiding symptoms and satisfied parents. Whenever possible an uroflow was obtained during the follow up visits. Results: Forty-nine children met the inclusion criteria. All patients had marked penile curvature. Three patients had chromosomal abnormalities. The mean age at the time of surgery was 22 months (11-110) and the mean duration of follow-up 23.4 months (1-79). In 48 cases the urethral plate could be preserved without dividing it. The penile curvature was corrected with chordectomy alone in 10 patients 38 required a dorsal plication of the tunica albuginea and 1 required an additional ventral dermal graft. In 38 patients (77.5 %) the initial operation was successful and no further operations were needed. There were 8 urethrocutaneous fistulas, 3 dehiscences of the glans approximation. One patient suffered a wound infection and partial loss of the flap. Conclusions: One stage repair of mid and proximal hypospadias preserving the urethral plate and using a total preputial flap for the urethroplasty and coverage of the ventral penis is successful in 77.5 % of cases. Complications in the remaining patients were easily managed or did not require treatment. Compared to a planned 2 stage approach, the technique described in this report resulted in significantly fewer procedures till complete resolution of the problem.